LOCATING THE SCIENCE OF READING IN SANTO TOMAS CITY, PHILIPPINES: A CASE STUDY OF LITERACY APPROACHES : [MENELUSURI ILMU MEMBACA DI KOTA SANTO TOMAS, FILIPINA: STUDI KASUS TENTANG PENDEKATAN-PENDEKATAN LITERASI] - Jeremiah Paul Manuel; Rowena Cedo Madsa (Universitas Pelita Harapan, 2026)
The 2022 PISA assessment delivered a harsh truth about the literacy in the Philippines, raising urgency to recalibrate local reading initiatives. Since then, reading strategies have filled spaces in the reading field, including school-level up to national initiatives. This study seeks to determine whether these activities can be analyzed using the Science of Reading framework. The researchers employed a mixed-method research design, developing and validating a survey questionnaires and interviews among selected reading teachers. The results revealed that all five components of the Science of Reading are highly present in the local contexts. Additionally, five themes from the interviews were developed: differentiated reading instruction, targeted reading interventions, repetitive practice, needs-based instruction, and foundational skill development. These findings were analyzed, generating a framework that links the local initiatives to the Science of Reading. Abstrak Bahasa Indonesia Penilaian PISA 2022 memberikan kenyataan pahit tentang literasi di Filipina, meningkatkan urgensi untuk mengkalibrasi ulang inisiatif membaca lokal. Sejak saat itu, strategi membaca telah mengisi ruang dalam bidang membaca, termasuk tingkat sekolah hingga inisiatif nasional. Studi ini bertujuan untuk menentukan apakah aktivitas-aktivitas ini dapat dianalisis menggunakan kerangka kerja Ilmu Membaca. Para peneliti menggunakan desain penelitian metode campuran, mengembangkan dan memvalidasi kuesioner survei dan wawancara di antara guru-guru membaca terpilih. Hasilnya menunjukkan bahwa kelima komponen Ilmu Membaca sangat hadir dalam konteks lokal. Selain itu, lima tema dari wawancara dikembangkan: pengajaran membaca yang terdiferensiasi, intervensi membaca yang ditargetkan, latihan berulang, pengajaran berbasis kebutuhan, dan pengembangan keterampilan dasar. Temuan-temuan ini dianalisis, menghasilkan kerangka kerja yang menghubungkan inisiatif lokal dengan ilmu membaca.